2022
DOI: 10.1021/acsomega.2c02314
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining a Fraction of Sugarcane Wax Rich in Policosanol by Using Ethanol as Solvent: Results Interpretation through Hansen’s Solubility Theory

Abstract: Determination of the best condition for fractionation of degreased sugarcane wax for policosanol production using ethanol was investigated in this paper. The optimal conditions related to the dispersion time of wax in the solvent, ethanol degree, and solvent/wax ratio were 30 min, 90.03% v/v, and 14:1 v/w, respectively. The results were evaluated by measuring six response variables: higher fatty alcohol concentration, octacosanol concentration, impurity concentration (measured as α,β unsaturated aldehydes), yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…6 Previous studies identified long-chain aliphatic primary alcohols (policosanol), phytosterols (stigmasterol, β-sitosterol), triterpenoids, wax esters, aldehydes, and fatty acids in sugarcane-derived waxes. 1,9 Thus, phytosterols are valued as antioxidants due to their free radical scavenger capacity. 10 Moreover, the hypocholesterolemic effects of phytosterols and the anti-obesity properties of octacosanol have also been evidenced in previous studies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 Previous studies identified long-chain aliphatic primary alcohols (policosanol), phytosterols (stigmasterol, β-sitosterol), triterpenoids, wax esters, aldehydes, and fatty acids in sugarcane-derived waxes. 1,9 Thus, phytosterols are valued as antioxidants due to their free radical scavenger capacity. 10 Moreover, the hypocholesterolemic effects of phytosterols and the anti-obesity properties of octacosanol have also been evidenced in previous studies.…”
Section: ■ Introductionmentioning
confidence: 99%